A study to evaluate the location and frequency of denture-related ulcerations and postinsertion adjustments in complete denture patients - Saurabh Jain; Naveen Oberoi; Ashish Kumar; Aparna Aggarwal; Kanwalpreet Kaur (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Removable complete denture is one of the most common treatment modalities for completely edentulous patients. After denture insertion, patient very often faces problems with the denture even after complete care is taken during fabrication procedure. Most common complaint is traumatic ulcers. The present study aimed to locate the most common areas of ulcerations due to complete dentures, how frequently they occur and how many times patient visits for adjustment after insertion of complete denture. Materials and Methods: Two hundred and twenty-one patients were selected and were delivered complete dentures. Dentures were fabricated for all the patients. Each step of denture fabrication was controlled and guided by a prosthodontist. After placement of dentures, patients were evaluated at every recall visit and their dentures were adjusted. All the details of each visit (area of ulceration) and number of visits were recorded in a self-designed format. Descriptive statistical analysis was done using SPSS version 13 software. Chi-squared test was used to evaluate the correlation between mucosal injuries and postinsertion day and the relationship between lesions, patient age, and patient gender. Results: All the 221 patients required denture adjustment due to mucosal injuries. No significant difference was found between denture-related injuries between males and females. Injuries related to mandibular dentures were significantly higher than those related to maxillary dentures. In mandible, the most common area of mucosal injury is posterior one-third of alveololingual sulcus; while in maxilla, the most common area of mucosal injury is labial frenum. Conclusion: Postinsertion adjustments are an important aspect of rehabilitating patient with complete dentures. Most of the denture-related injuries were in limiting areas. Proper border molding techniques, accurate secondary impressions, and use of pressure indicating paste during denture insertion are main requisites for decreasing denture-related mucosal injuries.